The Effectiveness of Giving Boiled Eggs and Papaya Fruit Against Changes in Hemoglobin Levels in Pregnant Women at PMB F Bekasi - Rini Dwi Wahyuni; Vivi Silawati; Putri Azzahroh (International Journal of Midwifery and Health Sciences, 2023)
Background: Anemia in pregnant women is categorized as a global health problem. One of the factors for the high maternal mortality rate is the existence of high-risk pregnancies, diseases that are included in high-risk pregnancies, including anemia. The impact of anemia on pregnant women can cause obstacles to the growth of the fetus, both body cells and brain cells, abortion, prolonged labor due to lack of uterine thrust, bleeding, and infection. Purpose: To determine the effectiveness of boiled eggs and papaya fruit on changes in hemoglobin levels in pregnant women at PMB Fitria Wulandari, Bekasi in 2023. Methods: This study used a quasi-experimental pretest-posttest control group design. The research sample consisted of 30 respondents consisting of 15 people in the intervention group and 15 people in the control group. Sampling was done by using total sampling. Result: The average hemoglobin level of the control group before administration of Fe tablets was 10.687 gr/dl and after consuming Fe tablets was 10.773 gr/dl. While the average hemoglobin level in the intervention group before being given FE plus boiled eggs and papaya fruit was 10.473 gr/dl and after consuming Fe tablets plus boiled eggs and papaya fruit was 11.313 gr/dl. The statistical test results obtained p value: 0.000. Conclusion: There is an effectiveness in changing hemoglobin levels in pregnant women after consuming boiled eggs and papaya fruit at PMB Fitria Bekasi in 2023. Pregnant women can use eggs and papaya fruit as an alternative option to help increase hemoglobin levels.